Early motor skill interventions for children with autism; secondary effects on parents and families - Elliott, Leanne K; Weiss, Jonathan A; Lloyd, Meghann (European Journal of Adapted Physical Activity, 2023)
Motor skill interventions can improve the motor proficiency of children with autism, however, the secondary effects associated with these interventions are not well understood. The aim of this study is to describe 1) parents' experiences with an early motor skill intervention for their children with autism, and 2) the secondary effects of the intervention on parents and families. Parents (n = 8) of four-year-old children with autism who participated in a 12-week motor skill intervention were invited to take part in a semi-structured interview to discuss their experiences. The study was grounded in descriptive phenomenology. Three themes emerged from the data. Theme 1: Parent Attendance - observing the motor skill intervention was essential in order for parents to benefit from the experience themselves (e.g., socializing with the other parents), Theme 2: Eye-Opening Experience - the intervention shed light on the children's capabilities and the importance of motor skill development, Theme 3: Positive Experience - parents expressed a desire for more opportunities like this within the community. These findings indicate that early motor skill interventions for children with autism can also benefit parents and families. In order to better meet the needs of families of children with autism, clinicians should educate parents on the importance of motor skill development early, and highlight opportunities for active engagement at home and in the community.
Keywords: pohybová aktivita; postižené děti; rodina; Humans; Children with Disabilities; Family; Early Intervention, Educational; rodiče; lidé; Parents; raná péče; autistická porucha; Interviews as Topic; Autistic Disorder; předškolní dítě; motorické dovednosti; Motor Activity; Motor Skills; Child, Preschool; rozhovory jako téma